Research and publication trends on knee osteoarthritis and cellular senescence: a bibliometric analysis - Wang, Shuai; Yang, Jiyong; Xiang, Ruian; Li, Congcong; Li, Junyi; Shen, Xingxing; Liu, Wengang; Xu, Xuemeng (Frontiers in Physiology, 2023)
Background: Cellular senescence is associated with age-related pathological changes, senescent cells promote the development of knee osteoarthritis. A better understanding between knee osteoarthritis and cellular senescence may enhance the effectiveness of therapies that aim to slow or stop the progression of this disease. Purpose: This study aimed to systematically analyze and visualize the publication trends, research frontiers and current research hotspots of knee osteoarthritis and cellular senescence by using bibliometrics. Methods: The publication search was performed on the Web of Science Core Collection database for documents published from 1992 to 2023. VOSviewer, Citespace, R package Bibliometrix and Microsoft Office Excel were used to study the characteristics of the publications. The publication number, countries, institutions, authors, journals, citations and co-citations, keywords were analyzed. Results: A total of 1,074 publications were analyzed, with an average annual growth rate of 29.89%. United States accounted for the biggest contributor, ranked first in publications and citations. Publications of this field were published in 420 journals, OSTEOARTHRITIS and CARTILAGE was the most influential. A total of 5,657 authors contributed to this research. The most productive author was Lotz, MK (n = 31, H-index = 22, Total citation = 2,619), followed by Loeser, R.F (n = 16, H-index = 14, Total citation = 2,825). However, the collaboration between authors was relatively weak. Out of the 1,556 institutions involved, 60% were from the United States. Scripps Research ranked first with 25 papers and a total of 2,538 citations. The hotspots of this field had focused on the pathomechanisms (e.g., expression, inflammation, apoptosis, autophagy, oxidative stress) and therapeutics (e.g., stem cell, platelet-rich plasma, transplantation, autologous chondrocytes, repair), and the exploration of Senolytics might be the important direction of future research. Conclusion: Research on the cross field of knee osteoarthritis and cellular senescence is flourishing. Age-related pathomechanism maps of various cells in the joint and the targeted medicines for the senescent cells may be the future trends. This bibliometric study provides a comprehensive analysis of this cross field and new insights into future research.